Pharmacist interventions in improving clinical outcomes in patients with type 2 diabetes mellitus among the underrepresented population: A collaborative ambulatory care pharmacy practice (CAPP) approach - Mok Thoong Chong (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study was to evaluate the impact of pharmacist's interventions through a collaborative ambulatory care pharmacy practice (CAPP) model in patients with type 2 diabetes mellitus (T2DM) among the underrepresented population. Methods: Eligible patients were 18 years and older with a diagnosis of T2DM with or without comorbid cardiovascular disease risk factors. Patients were enrolled through routine primary care provider referrals. During a one-on-one, face-to-face scheduled clinic visit, the pharmacist provided a comprehensive medication management by reviewing vital signs and laboratory values, provided medication reconciliation and management, followed by medication counseling through a CAPP approach in a primary care setting. The pharmacist worked in close collaboration with the primary care provider to intervene on medication therapy through recommendations to initiate, adjust, modify, or discontinue drug therapy and order laboratory tests and drug concentration levels as appropriate. Each visit was documented as a "PharmD Progress Note" in the patient's electronic medical record. Follow-up visits were scheduled until patients' targeted treatment goals were achieved. Primary and secondary outcome data were collected and then analyzed. Findings: A pharmacist saw 47 patients over 12 months. Sixty-four percent of the participating patients were able to achieve targeted treatment goals. A statistically significant decrease in the mean change in hemoglobin A1c, diastolic blood pressure, fasting blood glucose, and triglyceride levels was observed from the baseline which was −2.3%, −7.75 mmHg, −76.1 mg/dL, and −55.5 mg/dL, respectively. No significant changes in other clinical outcomes were observed. Conclusion: The CAPP model demonstrated a significant reduction in clinical endpoints in patients with T2DM among the high-risk underrepresented population.